ahmedco31

100 Reputation

4 Badges

10 years, 239 days

MaplePrimes Activity


These are answers submitted by ahmedco31

yes my sum and products are finite and i agree that i should test them. thanks guys for you time and help

yes i noticed this bug but will it affect my differentiation or not?

i mean, are these results correct or this bug make them wrong?

i'm using maple 13 . thank you very much for your time. i still can't decide which mean should i consider so here you are the problem:-

enter this line to maple

w*(product(sum(p[i][j]*exp(-z[i][j]/t[j]), j = 1 .. m), i = 1 .. n))+(1-w)*[sum(sum(z[i][j], j = 1 .. m), i = 1 .. n

then differentiate w.r.t.     z[i][j]

then see the result and you will see the trailing tildes

yes i intented multiplications and lambda*b*j. i'll correct the code and try solve. if not i hope fsolve can do something

please please, i want to know which command (function) in maple should i use to solve these two equations. i posted the maple code of these equations before to copy them to your maple if you want. thanks

thanks edgar. i used exp for exponential fn. and i will use * for multiply. but which maple function can solve them?

yes robert that is what i'm saying. these are not differential equations.

here's the equations again. just copy them to maple and press enter

the first one:

n(-(2*(2*n+1))*exp(-2*`λa`(2*n+1))+(3*n+2)*exp(-`λa`(3*n+2))+(3*n+1)*exp(-`λa`(3*n+1))-(2*n+1)*e^(-`λa`(2*n+1)))+(2*(n-1))*exp(-`λa`(2*n+1))*n+(n-1)*exp(-`λa`(2*n+1))-(sum(-2*exp(-2*`λa`(2*n+i+1))*n-2*exp(-2*`λa`(2*n+i+1))*i-2*exp(-2*`λa`(2*n+i+1))+2*exp(-`λa`(2*n+i+2))*n+exp(-`λa`(2*n+i+2))*i+2*exp(-`λa`(2*n+i+2))+2*exp(-`λa`(2*n+i+1))*n+exp(-`λa`(2*n+i+1))*i+exp(-`λa`(2*n+i+1)), i = 1 .. n-1))-k(2*n+1)*(exp(-`λa`(2*n+1)))(exp(-`λb`(2*k+1))-exp(-`λb`(k+1))-exp(-`λbk`)+1)+(2*n+1)*exp(-`λa`(2*n+1))*(-(k-1)*exp(-`λbj`)+k-1+sum(exp(-`λb`(2*j+1))-exp(-`λb`(j+1)), j = 1 .. k-1))-(2*`λn`(n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λjb`)+k-1+sum(e^(-`λb`(2*j+1))-e^`λb`(j+1), j = 1 .. k-1)))*(exp(-2*`λan`))(n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λjb`)+k-1+sum(e^(-`λb`(2*j+1))-e^`λb`(j+1), j = 1 .. k-1)))+2*(lambda(n+1))(n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λjb`)+k-1+sum(e^(-`λb`(2*j+1))-e^`λb`(j+1), j = 1 .. k-1)))*(exp(-2*`λa`(n+1)))(n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λjb`)+k-1+sum(e^(-`λb`(2*j+1))-e^`λb`(j+1), j = 1 .. k-1)))-2*(lambda(2*n+1))(n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λjb`)+k-1+sum(e^(-`λb`(2*j+1))-e^`λb`(j+1), j = 1 .. k-1)))*(exp(-2*`λa`(2*n+1)))(n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λjb`)+k-1+sum(e^(-`λb`(2*j+1))-e^`λb`(j+1), j = 1 .. k-1))))/(1-(exp(-2*`λa`(n+1)))(1-exp(-2*`λan`))) = 0

 

the second one:-

n(e^(-2*`λa`(2*n+1))-e^(-`λa`(3*n+2))-e^(-`λa`(3*n+1))+e^(-`λa`(2*n+1)))-(n-1)*e^(-`λa`(2*n+1))-(sum(e^(-2*`λa`(n+i+1))-e^(-`λa`(2*n+i+2))-e^(-`λa`(2*n+i+1)), i = 1 .. n-1))+ke(e^(-`λb`(2*k+1))-e^`λb`(k+1)-e^(-`λkb`)+1)^(-`λa`(2*n+1))-e^(-`λa`(2*n+1))*(-(k-1)*e^(-`λbj`)+k-1+sum(e^(-`λb`(2*j+1))-e^(-`λb`(j+1)), j = 1 .. k-1))+be(k(-lambda(2*k+1)*e^(-`λb`(2*k+1))-lambda(k+1)*e^(-`λb`(k+1))+`λke`^(-`λbk`))-(k-1)*`λje`^(-`λbj`)-(sum(-lambda(2*j+1)*e^(-`λb`(2*j+1))+lambda(j+1)*e^(-`λb`(j+1)), j = 1 .. k-1)))^(-`λa`(2*n+1)) = 0

and my variables are (a,b)

plz some one tell me how can i solve them.

 

these equations are not differential equation and i don't have initial conditions how can i apply your code

thanks  Robert  i'll consider what you said.

thanks  Ternox . i will need a while to understand the code and apply it on my equations but when i do it i'll tell you what did i get.

thanks again. later

thank u. i will study your answer then i will reply.

ok thanks for your help

thankx man for your time. the first 9 equations have no solution so i added the last the 3 equations to make a solution. i'm sure that the 12 equations have solution since i solved the lower case (i=1,2 and j=1,2) by my hand and had a solution and i tryed solving them by maple and still no solution, why?

Page 1 of 1